2017
DOI: 10.1016/j.vaccine.2017.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the consequences of regional heterogeneity in human papillomavirus (HPV) vaccination uptake on transmission in Switzerland

Abstract: Regional variations in uptake diminish the overall effect of vaccination on HPV-16 prevalence in Switzerland, but the effect size is small. Cantonal efforts towards HPV-prevalence reduction by increasing vaccination uptake are impaired by cantons with low vaccination uptake. Although the expected impact on national prevalence would be relatively small, harmonization of cantonal vaccination programs would reduce inter-cantonal differences in HPV-16 prevalence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…To our knowledge, this study was one of the first to directly assess the prevalence of HPV and the effectiveness of the HPV vaccination directly in the population through the use of self-sampling in Switzerland. The other studies carried out on the subject had a more modeling objective of the prevalence of this infection after the introduction of the HPV vaccination in Switzerland without trying to measure it directly in the population [ 26 ], but one large study with another methodology had shown the same results in another Swiss county [ 27 ].…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…To our knowledge, this study was one of the first to directly assess the prevalence of HPV and the effectiveness of the HPV vaccination directly in the population through the use of self-sampling in Switzerland. The other studies carried out on the subject had a more modeling objective of the prevalence of this infection after the introduction of the HPV vaccination in Switzerland without trying to measure it directly in the population [ 26 ], but one large study with another methodology had shown the same results in another Swiss county [ 27 ].…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…As mentioned, there is regional and linguistic variation regarding vaccination uptake in Switzerland in the setting of different cantonal levels of school vaccination programmes39 78 and health authority support for vaccination programmes 79. On the other hand, we expect the prevalence of vaccine hesitancy and of its determinants to be relatively homogeneous across different geographical and language regions of Switzerland.…”
Section: Methods and Designmentioning
confidence: 99%
“…The most common reasons for women not being vaccinated against HPV, according to a 2014 survey, included being too old, lack of information, fear of side effects, being against vaccination in general or against HPV vaccination only, HPV vaccination felt to be unnecessary, and simple logistical issues,38 with 7% and 6% of women not vaccinated against HPV reporting that the physician or friends/family recommended against HPV vaccine, respectively. Further research has shown that living in cantons with school-based vaccination increases uptake of HPV vaccination 39 40. However, spatial variation modelling has shown that variables such as political opinion, religion and community opinion might be additional determinative factors in the presence of school-based vaccination programmes 40.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a mathematical model to describe the spread of nvCT in Sweden (table 1, online supplementary material S1). We implemented the spatial structure of Sweden consisting of 21 counties using a gravity model in a meta-population framework 15–17. We considered the population of Swedish sexually experienced heterosexual adults aged 15–29 years, subdivided into a low and a high sexual activity class (online supplementary figure S1).…”
Section: Methodsmentioning
confidence: 99%